Management of patients with malignancies and secondary immunodeficiencies treated with immunoglobulins in clinical practice: Long‐term data of the SIGNS study. (21st June 2017) - Reiser, Marcel; Borte, Michael; Huscher, Dörte; Baumann, Ulrich; Pittrow, David; Sommer, Claudia; Stangel, Martin; Fasshauer, Maria; Gold, Ralf; Hensel, Manfred
Abstract: Objective: We aimed to describe the current management and outcomes of patients with secondary immunodeficiencies (SID) on intravenous (IV) or subcutaneous (SC) immunoglobulins (IG) as maintenance therapy to prevent infections. Methods: Non‐interventional, prospective study (average follow‐up 20.5 months). Results: Of the 307 SID patients (mean age 63.7±14.4 years, 52% males, in 31% IG newly initiated), 95.4% received IV IG (mean dosing interval 4.6 weeks, average dose 199 mg/kg per 4 weeks) and 4.6% were treated with SC IG (2.6 weeks, 343 mg/kg per 4 weeks). Median IG through level at first documentation was 5.8 g/L and did not differ between IV and SC treatment or between underlying malignancies. In 24.1% of patients, treatment was interrupted temporarily, over a mean of 11.6±6.3 months. In patients with newly initiated IG treatment the 82% overall infection rate prior to treatment dropped to 21% at 1 year. Conclusions: Under clinical practice conditions, IG replacement therapy in SID patients was feasible, diminished infection rates and improved quality of life. Average IG doses were relatively low. Tolerability of IV IG treatment was excellent.